Catalytic Fast Pyrolysis of Corn Stalk for Phenols Production With Solid Catalysts - Wang, Lihong; Yi, Weiming; Zhang, Andong; Li, Zhihe; Cai, Hongzhen; Li, Yongjun (Frontiers in Energy Research, 2019)
Corn stover can be converted into a high market value product via catalytic fast pyrolysis. Specifically, through thermochemical conversion, corn stover can be converted into biocrude oil with a high content of unstable phenols, most notably active phenols, which can readily react with aldehydes to form phenolic resins. Therefore, the higher the content of active phenols, the greater the economic value of biocrude oil. This is due to the potential for active phenols to serve as value-added compounds in the form of phenolic resins. Catalysts can be incorporated to improve the reaction rate and product quality during fast pyrolysis. In this study, the effects of three solid catalysts, dolomite, red mud and HZSM-5(25), on the production of active phenols were investigated. The Folin-ciocalteu (FC) method and gas chromatography-mass spectrometry (GC-MS) were utilized to quantify and classify the types of phenolic derivatives present within the bio-oil. The results showed that active phenols with a content exceeding 70% constituted the largest fraction of the phenol derivatives. The formation of active phenols, especially B-phenols, was enhanced by the incorporation of the catalysts HZSM-5, red mud and dolomite. HZSM-5 and dolomite exhibited the best catalytic effect on the production of A-phenols and B-phenols, respectively. The highest content of C-phenols (47.16%) was achieved when red mud was utilized as a catalyst. With regard to the total content of active phenol derivatives, the catalytic effect of dolomite was better than that of HZSM-5 and red mud. The content of total phenols and active phenols increased as the reaction temperature increased from 450 to 600°C.